Analysis of Economic Analysis of Law Principle In Purchase Fuel By Application (Study of MyPertamina) (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2022)
Fuel has become a necessity in the society, fuel consists of subsidized and non-subsidized fuel oil. Subsidized fuel oil is intended for the middle class, this is the focus of the government so that fuel oil is right on target. One of the government's efforts is the plan to use MyPertamina to purchase subsidized fuel oil, but this raises pros and cons in the community. The purpose of this research is how the principle of efficiency in the economic analysis of law views this government plan. The author uses normative research methods in this paper because it discusses the principles, norms with library data collection techniques or literature which is then analyzed using perspective analysis techniques. The result of this study is that this policy plan is not yet fully efficient because because of this plan, some people are troubled by several things, for example the lack of socialization about this, the prohibition of using cellphones at gas stations or obstacles when using MyPertamina.